Interaksi Edukatif Guru Pendidikan Agama Islam Dan Siswa Dalam Membentuk Kepribadian Muslim - An Nahdliyah, Khumairoh; Naelasari, Desy (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2024)
This research examines the educative interaction of Islamic Religious Education teachers in shaping students' Muslim personality at SMPN 1 Ngoro Jombang. The background of this research is the importance of educative interaction in the learning process and the formation of students' Muslim personality. The research method uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the educative interaction of PAI teachers included seven components: objectives, teaching materials, teaching and learning activities, methods, tools, teaching resources, and evaluation. The formation of students' Muslim personality is focused on four aspects: honesty, responsibility, religion, and courtesy. Effective educative interaction proved to play an important role in shaping students' Muslim personality, although there are still challenges in its implementation. The conclusion of this study emphasizes the importance of the role of PAI teachers in designing and implementing effective educative interactions to shape students' comprehensive Muslim personality, covering spiritual, moral, and social aspects.